Microbiological profiling of food waste compost / Lawal Saheed Folorunsho - Lawal Saheed , Folorunsho (2019)
Increase in food waste is a growing problem in most developing countries including Malaysia. The improper and inadequate use of landfill treatment systems in the country elucidate high release of various environmental contaminants such as leachate which contaminate groundwater, potential release of toxic gases and other odour producing organic pollutants. Therefore, employing composting as a potentially viable means to reduce waste disposed through landfilling may yield fruitful results. However, this composting has its limitations because the process may fail to inactivate all of the pathogenic microorganisms that may be present in the food waste. The resulting food waste compost may then pose a public health risk by cross contaminating the food crops. Thus, this study aims to assess the microbial risk by identifying and characterising the potential microbial hazards and risk associated with food waste compost, as well as to isolate beneficial bacteria with antimicrobial activity against the major foodborne pathogens associated with the food waste compost. The microbial profiling identified Clostridium sp. as a potential high risk microbial hazard associated with food waste compost, followed by Listeria monocytogenous, Escherichia coli, Salmonella, Bacillus cereus and Vibrio sp. to be categorised as the microbial hazards with medium risk and Staphylococcus aereus as low risk. The matured food waste composts tested in this study demonstrated high count of heterophilic bacteria (Mean = 2.5×104 CFU/g) and fungi (Mean = 3.1×104 CFU/g). Although Enterobacteriaceae (Mean = 1.6 ×104 CFU/g) and total coliforms (Mean = 1.1×104 CFU/g) were detected in the samples, E. coli, Salmonella, and Vibrio sp., were not detected in the matured food waste compost. Of the 91 isolates collected from the composts, results showed that about two-third of the isolates (n=56; 62%) were Gram positive bacteria. Maldi-ToF was only able to identified 21 isolates (23%) of the compost-borne bacteria. Bacillus sp. is the most commonly identified bacterial genera of these identified bacteria. From the 91 compost-borne isolates that were tested to determine the antimicrobial activity against the nine selected foodborne pathogens (various type of pathogenic E. coli, B. cereus, P. mirabilis and Salmonella), nine isolates (10%) showed antimicrobial activity against the foodborne pathogens tested. These nine isolates were identified to be Klebsiella aerogenes, Lysinibacillus fusiformis, Shigella flexneri, Klebsiella pneumoniae, E. coli, Enterobacter aerogenes, Shigella dysenteriae, Enterobacter cloacae and Pantoea agglomerans. In conclusion, this study showed that improperly composted food waste could pose a significant public health risk if the compost is used for food crops farming. Although the thermophilic stage during the composting has been thought to be the major inactivation mechanisms of pathogenic microorganisms, the survival of pathogens during the composting process could be very complex and involves numerous physicochemical factors as well as the antagonistic effect of other microorganisms present in the compost. Thus, this study clearly showed that the anti-pathogenic bacteria are present in the food waste compost. These beneficial bacteria could be further explored for application to enhance the inactivation rate of pathogenic bacteria during food waste composting.